ANALYSIS OF COLLEGE STUDENTS’ DIFFICULTIES IN MATHEMATICS EDUCATION OF THE CLASS 2013IN SEMBILANBELAS NOVEMBER UNIVERSITY INSOLVING THE PROBLEM OF ONE-WAY ANALYSIS OF VARIANCES(ONE WAY ANOVA)ON APPLIED STATISTICS COURSE - Supratman Supratman; Herlina Herlina (USN Kolaka, 2017)
Statistic is one of the branches of applied mathematical science developed by Karl Pearson (1857-1936). Applied statistic is the study of the application of statistical use. Many students think that applied statistic course are difficult, which can only masteredby smart students. Even the students’ anxiety arises every time they are dealing with the applied statistic course. This anxiety due to the acquisition of applied statistic value is generally lower compared to the acquisition of the other course’s value, it is seenthat many students who have not been able to solve the problem related to the analysis of one-way varience (One-Way Anova). This research is done to identify, recognize, analyze, then got a result of research about students’ difficulties in solving the problem of one-way variance analysis. Specifically the purpose of this study is to determine the difficulties that experienced by the students of mathematics education of sembilanbelas November University, Kolaka, in solving the problem of analysis of oneway variance inapplied statistic course, as well as the efforts that can be done to overcome these difficulties. To realize it in this research, the researcher use verifikatif qualitative design to describe the actual situation and verify it, this research tries todescribe the actual requirement for the learners of mathematics which of course through the requirement analysis process then verified in order to find an ideal learning design. This research will be conducted in scientific procedures in the academic realm. This research will be carried out at Sembilanbelas November University, kolaka, with active students of Teachers and Education Faculty on mathematics, alumni, and lecturer of Teacher and Education Faculty on mathematics study program will be chosen as informant with purposive sampling technique. In depth interview, unstructured observation, and dokumen analysis will be pplied as the technique of data collection in this research, while the instruments to be used in the data collection are semi-structured interview guides, observation sheets, and documents. In analyzing the data, the researcher uses content-analysis that systematically and objectively identifies a specific message characteristic. From the results obtained, that there are three types of mistakes made by the students, such as, there are ten students who make a conceptical mistake that is equal to 29,41%, twentytwo students or equal to 64,71% who make a mistake in principle, while those who make verbal errors as much as nineteen students or equal to 55,88%.